NILAI-NILAI AGAMA DAN PEMBINAAN KUALITAS MANUSIA - Aminullah Cik Sohar (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
In today's era of development requires qualified human beings. Development is also necessary to the success of the participation of all the people and the organizers negaea the mental attitude and the spirit of obedience and discipline and to realize the implementation of the development.In the perspective of religion is also a necessity in mental development that can not be separated from the physical qualities of human development. Human qualities lies in the extent to which humans are able to live the values of religion and religious values actualized in the form of behavior.Through the educational process of human consciousness will grow and evolve. Development in Indonesia are in need of human beings berkalitas are realized through the national education.